La maestría de la Universidad de La Habana en Microbiología: su calidad e impacto. - Rojas Badía, Marcia M.; Rojas Hernández, Nidia Mercedes; Romeu Álvarez, Beatriz; Heydrich Pérez, Mayra; Ramos Leal, Miguel; Roque Quintero, Annele; Coto Pérez, Orquidea; Hernández Rodríguez, Annia (Cuban Journal of Biological Sciences / Revista Cubana de Ciencias Biológicas, 2014)
The Master program in Microbiology is developed in Biology Faculty, University of Havana. Professionals from several sectors of research, services, production, teaching and other have been inserted in the Program. They are form different institutions of the country that are working in areas of biological sciences. The program has five specializations fields. That is why the master is the unique Master in Microbiology with a wide range of thematic in microbiology and virology. The master program offers to graduated greater independence and originality in the analyses of particular problems of their science than themselves before, with a multidisciplinary approach. All of them are warranted through the lectures and researching credits. Also, it is articulating with the PhD program, mainly on Biological Science. The professional development of master graduated will have better quality and they will prepare for this new goal. The inquiry carried out demonstrated the pertinence and the high impact of the program in Master in Microbiology, recognized as an Excellence Program for a second time in 2012.